Service-dominant logic and licensing in international B2B markets - Olavi Uusitalo; Kjell Grønhaug (jbm - Journal of Business Market Management, 2012)
This paper asks whether the service - dominant logic is superior to the traditional goods - dominant logic for the use of licensing to commercialize new technologies internationally - and why so. To answer this question two case of licensing float glass, a float glass manufacturing technology and Benecol, a process to manufacture cholesterol lowering ingredient for food, are examined and contrasted. The findings indicate that the service - dominant logic yields advantages. Licensing logic for success in technology transfer is suggested.
urn:nbn:de:0114-jbm-v5i4.330
Keywords: 650; licensing; service dominant logic; international business